Mobile reading as social and embodied practice. Issue 2 (4th May 2017) - Hellermann, John; Thorne, Steven L.; Fodor, Peter
Abstract: Literacy, and particularly reading, is critical to success in schooling and full participation in contemporary societies. As one of the primary skills needed to develop proficiency in a language, the study of reading in additional languages has attracted significant research attention. Focusing on behaviourally visible and locally occasioned literacy events, this paper reports on an analysis of how public interactional practices for out-loud reading by small groups of English language learners facilitate the routinisation of interactional practices. The learners are participants in a mobile augmented reality (AR) activity that involves walking around a university campus in order to complete five serial tasks. Data come from video recordings of the game playing of eight groups (16 h of data) and their associated transcripts, analysed according to the principles of ethnomethodological conversation analysis. Results show that written texts that are part of the activity are given local meaning via various interactional practices that include public reading, co-reading and other embodied practices. We show how these dynamics of re-textualisation provide evidence for developing interactional practices over the course of the five tasks that are part of the activity.